Dating the Thera (Santorini) eruption: archaeological and scientific evidence supporting a high chronology. (December 2014) - Manning, Sturt W.; Höflmayer, Felix; Moeller, Nadine; Dee, Michael W.; Ramsey, Christopher Bronk; Fleitmann, Dominik; Higham, Thomas; Kutschera, Walter; Wild, Eva Maria
Abstract : The date of the Late Bronze Age Minoan eruption of the Thera volcano has provoked much debate among archaeologists, not least in a recent issue of Antiquity ('Bronze Age catastrophe and modern controversy: dating the Santorini eruption', March 2014). Here, the authors respond to those recent contributions, citing evidence that closes the gap between the conclusions offered by previous typological, stratigraphic and radiometric dating techniques. They reject the need to choose between alternative approaches to the problem and make a case for the synchronisation of eastern Mediterranean and Egyptian chronologies with agreement on a 'high' date in the late seventeenth century BC for the Thera eruption.